Effects of cadmium toxicity on the morphology of Bidens pilosaL - Vilca Valqui, Nuri Carito (2022)
Cadmium is a metal that affects natural resources, plants and human beings. Therefore, different methods have been sought to mitigate the problem, one of them is phytoremediation that makes use of species that have the potential to accumulate the heavy metal in their plant tissues. The objective of this research was to evaluate the effect of cadmium toxicity on the morphology of cadmium cadmium plants (Bindes pilosa L.). The plants were planted in two types of substrate with pH 6.27 and 5.53, adding different concentrations of cadmium chloride (CdCl2) (0, 5 and 10 ppm) inside a greenhouse; where there were 6 treatments with 5 replicates, thus having 30 experimental units. Morphological parameters and Cd concentrations in the root and foliar parts were evaluated. From the results obtained, the cadillo planted in the substrate with pH 5.53 without CdCl2 had greater height with 27.18 cm, with the same substrate plus 10 ppm of CdCl2 higher values were obtained in the variables; number of shoots (16 shoots), foliar fresh weight (26.70 g), foliar dry weight (10.92 g), root fresh weight (5.77 g), root dry weight (1.04 g) and root length (26.90 mm). Regarding the accumulation of Cd in plant tissues, a higher concentration was obtained in the foliar part (7.27 ppm) and less in the root (2.57 ppm). It is concluded that this species could be useful in the phytoremediation of Cd-contaminated soils.